UJI KEBERHASILAN SAMBUNG PUCUK LANGSAT DENGAN BERBAGAI PEMOTONGAN DAUN ENTRES - ARIANTO, EKO (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTThis study aimed to determine the effect of cutting leaves on the success of Lansium shots grafting. This research was conducted in Sungai Belidak Village Sungai Kakap Subdistrict, Kubu Raya District on June 12th 2018 – September 12th 2018. The method used in this study was a field experiment method with a completely randomized design (CRD), which consisted of 5 treatments, namely: p0 (without cut), p1 (leaves are completely cut shortly before splicing), p2 (cut ½ from the leaf just before splicing), p3 (leaves are completely cut 5 days before splicing with entres still in the parent tree), p4 (cut ½ from part leaves 5 days before connecting with entres still in the parent tree). Each treatment had 5 replications and each treatment consisted of 5 sample plants so that a total of 125 plants. The variables observed consisted of: percentage of graft success (%), number of leaves formed (leaves), increase of scion length (cm), time of shoots emergence (days), number of shoots emerged (shoots), time of leaf fall (days) and number fallen leaves (leaves). The results showed that the cutting of leaves of the entres had no significant effect on all observation variables.Keyword: Lansium, Leaf Cut, Shoots Grafting